1997
DOI: 10.1063/1.119694
|View full text |Cite
|
Sign up to set email alerts
|

Exciton saturation in room temperature GaAs/AlGaAs multiple quantum wells

Abstract: We report time resolved studies of optically induced circular dichroism in room temperature GaAs/AlGaAs multiple quantum wells to resolve spin-dependent and spin-independent contributions to exciton saturation. Phase-space filling and Coulomb contributions were separated by spin dependence while the effects of broadening and screening were distinguished using different pulse bandwidths. Bound and free carrier contributions were compared by observing the temporal dependence of the circular dichroism on femtosec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…9 The operation and optimization of these devices rely on an understanding of the mechanisms that contribute to bleaching of the exciton absorption feature at room temperature. Previous work has shown that the relative contributions of the various mechanisms which cause bleaching can be distinguished by the use of circularly polarized light 10,11 and different laser pulse widths 12 in pump-probe measurements. This article describes pump-probe measurements in GaAs/AlGaAs MQWs using both picosecond and femtosecond duration pulses, as a function of wavelength, polarization, bandwidth, carrier density, and well width in order to quantify the individual contributions to excitonic optical nonlinearities.…”
Section: Introductionmentioning
confidence: 99%
“…9 The operation and optimization of these devices rely on an understanding of the mechanisms that contribute to bleaching of the exciton absorption feature at room temperature. Previous work has shown that the relative contributions of the various mechanisms which cause bleaching can be distinguished by the use of circularly polarized light 10,11 and different laser pulse widths 12 in pump-probe measurements. This article describes pump-probe measurements in GaAs/AlGaAs MQWs using both picosecond and femtosecond duration pulses, as a function of wavelength, polarization, bandwidth, carrier density, and well width in order to quantify the individual contributions to excitonic optical nonlinearities.…”
Section: Introductionmentioning
confidence: 99%
“…The blueshift of the condensate increases linearly with the pumping intensity, in the case of ring-like excitation, showing the linear increase of the mean number of condensed polaritons. In the case of Gaussian excitation, the blue shift is strongly affected by the reservoir: it is twice as large as in the ring-excitation case and slowly saturates above threshold, indicating that exciton saturation has been reached [29].…”
mentioning
confidence: 99%
“…At ⌬t ϳ 0 ps, both I dt ͑ Ϯ ͒ increases due to the spin-independent CS. 11 The difference between I dt ͑ + ͒ and I dt ͑ − ͒ is seen up to ⌬t ϳ 350 ps. In Fig.…”
mentioning
confidence: 96%
“…2 In this context, optical nonlinearity and circular dichroism induced by spin-polarized electrons or excitons are important and essential. Recently, many experiments of time-resolved optical spectroscopy have explored exciton [3][4][5][6][7] and spin [8][9][10][11] dynamics in semiconductors and their quantum structures in depth. The mechanisms responsible for modulation of exciton resonance absorption at low excitation levels and low temperatures are phase space filling ͑PSF͒ and Coulomb screening ͑CS͒ which can be separated into short-ranged exchange interaction and longranged Coulomb correlation between exciton-exciton and free electron-hole pairs.…”
mentioning
confidence: 99%